2018
DOI: 10.1111/gbb.12541
|View full text |Cite
|
Sign up to set email alerts
|

Stress early in life leads to cognitive impairments, reduced numbers of CA3 neurons and altered maternal behavior in adult female mice

Abstract: The hippocampus is a crucial part of the limbic system involved both in cognitive processing and in the regulation of responses to stress. Adverse experiences early in life can disrupt hippocampal development and lead to impairment of the hypothalamic‐pituitary‐adrenal axis response to subsequent stressors. In our study, two types of early‐life stress were used: prolonged separation of pups from their mothers (for 3 hours/day, maternal separation, MS) and brief separation (for 15 minutes/day, handling, HD). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 105 publications
2
16
0
Order By: Relevance
“…The specific aim of the present study was to characterize the expression of immediate early genes in the prefrontal cortex of adult female mice as a marker of modified neuroplasticity elicited both by stress early in life and by previous social interaction. In addition, we analyzed the expression of these genes in the dorsal hippocampus, as a region affected by stress early in life, as demonstrated by us previously [15]. In that study [15], by means of the same model of stress in females, we showed that prolonged maternal separation reduces the number of mature neurons in the CA3 area of the dorsal hippocampus and impairs long-term spatial and recognition memory.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…The specific aim of the present study was to characterize the expression of immediate early genes in the prefrontal cortex of adult female mice as a marker of modified neuroplasticity elicited both by stress early in life and by previous social interaction. In addition, we analyzed the expression of these genes in the dorsal hippocampus, as a region affected by stress early in life, as demonstrated by us previously [15]. In that study [15], by means of the same model of stress in females, we showed that prolonged maternal separation reduces the number of mature neurons in the CA3 area of the dorsal hippocampus and impairs long-term spatial and recognition memory.…”
Section: Introductionmentioning
confidence: 79%
“…In addition, we analyzed the expression of these genes in the dorsal hippocampus, as a region affected by stress early in life, as demonstrated by us previously [15]. In that study [15], by means of the same model of stress in females, we showed that prolonged maternal separation reduces the number of mature neurons in the CA3 area of the dorsal hippocampus and impairs long-term spatial and recognition memory. Thus, in the present study, we wanted to estimate how these observed behavioral changes in emotional states are related to the neuroplasticity of the dorsal hippocampus.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Two papers in this issue examine factors that can disrupt a behavior that is (at least in most laboratory rodents) uniquely female—maternal care—which can have long‐lasting effects on offspring development and mental health. Reshetnikov et al find that prolonged separation from their pups during the first 2 weeks of life causes a robust decrease in pup licking, an effect accompanied by cell loss in the hippocampus and spatial memory deficits. Poor maternal care was also observed in mice with a double knockout (dKO) of two diacylglycerol kinase genes (eta and iota) .…”
mentioning
confidence: 99%